The Management of Intellectual Capital in the Resolution of Social Problems - López de Castro, Sandra (Revista Arbitrada Formación Gerencial, 2022)
Intellectual capital management is developed based, on the one hand, on the eclecticism of administrative theories and, on the other, on knowledge management. It is, therefore, a process that involves integrating organizational variables (tasks, structure, people, technology and environment) in order to achieve quality results for the generation of knowledge and its conversion into entrepreneurial initiatives that can provide answers to social needs.